Peningkatan Kapasitas Lansia Melalui Komunitas 'Sekolah Eyang' di Desa Sumberlesung, Kecamatan Ledokombo, Kabupaten Jember - Tista Arumsari; Kusuma Wulandari; Sari Dewi Poerwanti (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2023)
The 'Grandmother School' community is a place for the elderly to get education and actualize it. Elderly people are one of the most vulnerable groups in society and tend to experience discrimination, stereotypes, and social exclusion due to their aging condition. The presence of this community has an impact on increasing the capacity of elderly members of the community. Opportunities to actualize and re-learn that are accommodated by the community enable them to fight against various social constructions that undermine their potential. The research method used is qualitative research. Data collection is done through observation, interviews, and documentation. After the data is collected, it is presented descriptively and analyzed based on the data analysis method described by Miles, Huberman, and Saldana (2014) to draw conclusions. The purpose of this study was to identify and describe the capacity building of the elderly through the 'Grandmother School' community in Sumberlesung Village, Ledokombo District, Jember Regency. Keywords : Elderly; The 'Grandmother School' Community; Capacity Building